Ethical considerations in qualitative study - Mohd Arifin, Siti Roshaidai (IIUM Press, 2018)
The protection of human subjects through the application of appropriate ethical principles is important in all research study. In a qualitative study, ethical considerations have a particular resonance due to the in-depth nature of the study process. The existing ethical guidance for undertaking qualitative research often provide general guidelines rather than focusing on how to apply it in practice, particularly when interviewing vulnerable group of women. The aim of this paper is to present my own experience of conducting 33 individual face to face interviews on the women’s experience of postnatal depression across three different cultural backgrounds in Malaysia. This paper reflects on the strategies that can be adopted by a qualitative researcher to ensure that their participants’ identity is protected throughout recruitment and dissemination process, to deal with participants from different cultural backgrounds, and to handle and manage distress during interview. The consideration of ethical issues is crucial throughout all stages of qualitative study to keep the balance between the potential risks of research and the likely benefits of the research.